DNase increases the efficacy of antimicrobial photodynamic therapy on Candida albicans biofilms - Panariello, Beatriz H.D. [UNESP] (2019)
Antimicrobial Photodynamic Therapy (aPDT) has been proposed as a means to treat Candida infections. However, microorganisms in biofilms are less susceptible to aPDT than planktonic cultures, possibly because the matrix limits the penetration of the photosensitizer. Therefore, the goals here were: (1) to target biofilm matrix components of a fluconazole-susceptible (S) and a fluconazole-resistant (R) C. albicans (Ca) strains using the hydrolytic enzymes β-glucanase and DNase individually or in combination; (2) to apply the best enzyme protocol in association with aPDT mediated by Photodithazine® (PDZ); (3) to verify under confocal microscope the penetration of PDZ in biofilms pre-treated or not with DNase at different periods of incubation. CaS and CaR 48h-old biofilms were incubated with the hydrolytic enzymes (5 min) and evaluated by cell viability, biomass, and matrix components. DNase showed the best outcomes by significantly reducing extracellular DNA (eDNA) and soluble proteins from the matrix of both strains; and water-soluble polysaccharides from CaR matrix. Subsequently, 48h-old biofilms were incubated with DNase for 5 min, followed by incubation with PDZ for 20 min and exposure to LED light (660 nm, 50 J/cm²). Controls were biofilms treated only with aPDT without DNase, PDZ only, PDZ + DNase, light only, light + DNase, and biofilm without treatment. Pre-treatment with DNase allowed PDZ penetration into deeper biofilm layers, and the aPDT effect was enhanced, showing a significant reduction of the cell viability (p = 0.000) and eDNA amounts (p ≤ 0.047). DNase affected the matrix composition improving the penetration of the photosensitizer, thereby, improving the effectiveness of subsequent aPDT.